Homework Help

Prove the trig identity: cos(-x)+cos(pi-x)=cos(pi+x) + cos(x)

sasuke24's profile pic

Posted via web

dislike 1 like

Prove the trig identity: cos(-x)+cos(pi-x)=cos(pi+x) + cos(x)

1 Answer | Add Yours

crmhaske's profile pic

Posted (Answer #1)

dislike 1 like

`cos(-x) = cos(x)`

`cos(pi-x)=-cos(x)`

`cos(pi+x)=-cos(x)`

Therefore:

`cos(x)-cos(x)=-cos(x)+cos(x)`

`0=0`

Since the left side equals the right side, the original equation is true.

Sources:

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes